The comparative effectiveness of stress inoculation training and creative visualization in reducing teacher stress - Adefuin, John Jaworski N. (Animo Repository, 1997)
This study investigates the comparative effectiveness of stress inoculation training and creative visualization in reducing teacher stress.The subjects were 36 female public school teachers, grouped into two treatment groups, and one control group using match group method. There were 12 participants in each of the three groups, namely: stress inoculation, creative visualization and control group. The Teacher Occupational Stress Factor Questionnaire (TOSFQ), constructed by E.H. Clark (1980) was utilized to measure the level of stress of the participants.The first experimental group experienced Stress Inoculation Training (SIT) that lasted for seven days or equivalent to seven sessions with one hour for each meeting. The second experimental group had creative visualization for six days with one hour per session. In the case of the control group, no intervention was administered. All data were subjected to the t-test for uncorrelated data and one-way analysis of covariance (ANCOVA), and computed using Least Significant Difference (LSD) at .01 confidence level.The findings revealed that significant differences (p .01) were noted between the pretest and posttest scores in the five factors measuring teacher stress of the stress inoculation and creative visualization groups. For the control group, no difference (p .05) was observed between their pretest and posttest scores except in the two teacher stress factors, namely, group instruction and creative visualization. These differences (p .05) in the two stress factors were attributed to the increase in the stress level scores. This means that the control group's teacher stress levels for these factors had increased. The results further suggested that stress inoculation training and creative visualization were both effective tools in reducing teacher stress. The delayed posttest, administered after one month, revealed no significant difference (p .05) in all the five factors of teacher stress between the stress inoculation and creative visualization group. The outcome proved the effectiveness of stress inoculation training and creative visualization in maintaining the stability of the stress levels of the participants after one month.Finally, it could be concluded that SIT and creative visualization are both effective in reducing teacher stress. However, creative visualization has greater therapeutic efficacy compared to stress inoculation training in reducing teacher stress.